BLEPHAROPLASTY (EYELID PLASTIC) – THEORETICAL BASIS, TECHNIQUE AND COMPLICATIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Blepharoplasty is eye eyelids to age related and functional defects to correct aimed at aesthetic-reconstructive surgery The article eye eyelids to age related changes etiology and pathogenesis , as well as blepharoplasty instructions and Contraindications have been studied . The operation main technician stages : marking , anesthesia , skin and adipose tissue resection , scar to put processes in detail illuminated . Postoperative care rules and possible was complications ( hematoma , infection , scarring) deformations and others ) see was published . In the study blepharoplasty efficiency and dangerous sides analysis made.